Gallic acid inhibits neuroinflammation and reduces neonatal hypoxic-ischemic brain damages - Dong, Xiangjun; Luo, Shuyue; Hu, Dongjie; Cao, Ruixue; Wang, Qunxian; Meng, Zijun; Feng, Zijuan; Zhou, Weihui; Song, Weihong (Frontiers in Pediatrics, 2022)
Neuroinflammation is a leading cause of secondary neuronal injury in neonatal hypoxic ischemic encephalopathy (HIE). Regulation of neuroinflammation may be beneficial for HIE and its secondary complications. Gallic acid (GA) has been shown to have an anti-inflammatory and antioxidant effect. In this report we found that oxygen-glucose deprivation and /re-oxygenation (OGD/R)-induced cell death, the generation of excessive reactive oxygen species (ROS) and inflammatory cytokines by microglia was inhibited by GA treatment. Furthermore, GA treatment reduced neuroinflammation and neuron loss, as well as alleviate motor and cognitive impairments in rats with hypoxic-ischemic brain damage (HIBD). Together, our study reveals that GA is an effective regulator of neuroinflammation and has a pharmaceutical potential for HIE therapy.